1991
DOI: 10.1016/0014-5793(91)80617-c
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐dependent cationic channels formed by a cytolytic toxin produced by Gardnerella vaginalis

Abstract: A eytotytis toxin gr~duecd by C, vrr#innli.r WBX incorporated in ~rrislsirl membrnnrs and giant lipotemca. The taxin t'otmed ionic &arm& when incr)rpQrrrrd in lipid bilryera. 7% elce~ricrl properties er such channels were rludicd. Currcnr rccordn rcw~ltd 11 unitary eondurlunec of I 26 pS (in x~mmctricsl ISO mM KCI), The @en ntuls prebirbility of the cy~al&n formed rhennclw wax n Bune~lan of the Lpplicd membrane patcnrial.The permeability ratia alMans to ~nionx wxx estimated IQ bc 6.5, I INTROBUCTIONGarcim=@lla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(1 reference statement)
1
4
0
Order By: Relevance
“…It implies that the pore formed by CTox has a diameter between these two values, in agreement with Kretzschmar et al [12]. This range fits well with the conductance of 125 pS and with the Ca 2÷permeability found in the electrophysiological measurements of CTox-formed pores in lipid membranes [7]. As described before, the lytic activity of CTox is not coupled with direct phospholipase activity [5].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It implies that the pore formed by CTox has a diameter between these two values, in agreement with Kretzschmar et al [12]. This range fits well with the conductance of 125 pS and with the Ca 2÷permeability found in the electrophysiological measurements of CTox-formed pores in lipid membranes [7]. As described before, the lytic activity of CTox is not coupled with direct phospholipase activity [5].…”
Section: Discussionsupporting
confidence: 87%
“…The presence of ionic channels on the membrane of giant liposomes containing CTox has been revealed in a previous work [7], using the patch-clamp technique. A highly homogeneous cationic (PK/Po = 6.5) conductance population, of 125 Jr 4 pS was recorded.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The value found by the thermal denaturation midpoint method was 42 mol% (234). The cesium chloride buoyant density gradient centrifugation method gave values of 43.1 (82) Investigations have been limited by difficulties experienced in lysing G. vaginalis (80,82,174 (150) studied the electrical properties of ionic channels formed upon introduction of the cytolytic toxin into artificial membranes. The successful incorporation into liposomes indicated that the channel-forming conformation of the protein is independent of the erythrocyte target specificity of the cytotoxin.…”
Section: Introductionmentioning
confidence: 99%